Filogenia e Diversificação do Gênero Arthrocereus (Cactaceae): um enfoque nas relações de espécies endêmicas dos Campos Rupestres - Costa, Ágatha Cristina Marinho da (Universidade Federal de São Carlos, 2024)
Phylogenomics is one of the most widely used approaches today for proposing phylogenetic relationships due to their practicality, reliability, and precision of results. This study uses genomic data to present the first estimated phylogeny for the genus Arthrocereus. Arthrocereus comprises five species and three subspecies, predominantly occurring in Campos Rupestres. The hypotheses for this work included the monophyly of the genus Arthrocereus, its species and subspecies, and the sharing of a common ancestor between Arthrocereus and the genera Harrisia and Echinopsis. Six phylogenetic trees were obtained at the end, with datasets separated into genetic data from exons, on-target regions captured by probes that retrieved 591 regions of interest, and flanking regions, exons, introns, and intergenic regions. The results confirmed that the genus Arthrocereus is monophyletic. However, there are still inconsistencies regarding the sister groups of the genus, particularly its relationship with the genus Harrisia. The relationship among the species A. melanurus subsp. magnus, A. glaziovii, A. rondonianus, A. melanurus subsp. odorus, and A. grandiflorus was recovered with low support and extremely short branches, which may result from incomplete lineage sorting, hybridization, or rapid speciation, causing incongruence among gene trees. The results obtained in this study are crucial for identifying relationships among the taxa in this group and potential cryptic species and providing essential information for the conservation of these species.
Phylogeny and Diversification of the Genus Arthrocereus (Cactaceae): A Focus on the Relationships of Endemic Species from the Campos Rupestres
Keywords: Filogenia; Cactaceae; Arthrocereus; Filogenômica; Cerrado; Phylogeny; Phylogenomics; Rupestrian fields; Campos rupestres; CIENCIAS BIOLOGICAS::BOTANICA